Applying Fuzzy Fault Tree Method to Evaluate the Reliability of College Classroom Teaching - Wang, Liangliang; Fan, Mingfang; Zhang, Feng (Frontiers in Psychology, 2021)
The evaluation of classroom teaching quality is closely related to the development of higher education as a scientific and effective evaluation system can provide a solid foundation for formulating educational policies. Therefore, an evaluation model of classroom teaching quality in colleges and universities is established based on the fuzzy fault tree theory with “classroom teaching failure” as the top event to effectively evaluate the reliability of college classroom teaching and optimize teaching strategies. In consideration of the lack of availability and dynamics of classroom teaching data, fuzzy numbers are used to describe the probability of underlying events. In addition, the top event probability of the fuzzy fault tree is calculated by the double-layer Monte Carlo method, which makes the analysis of the classroom teaching effect based on the fuzzy fault tree is reasonable. In summary, the quantitative evaluation system of classroom teaching quality based on fuzzy fault trees can evaluate classroom teaching more comprehensively and dynamically and help to improve the teaching quality of higher education.